Assessment of suman during storage - Concepcion, Cherry Mae Ga (2006.)
The study focused on the assessment of suman during nine (9) day storage at room (29 degree celcius to 30 degree celcius) temperature.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Suman